Land pooling in South Asia lessons learned for equitable, participatory, and inclusive urban expansion - Ballaney, Shirley; Faust, Amy; Swarankar, Ramesh C.; Belliappa, Saswati Ghosh (South Asia working papers)
Trust between stakeholders is a prerequisite to enable the governments to scale it up for land development and urban expansion. The case study provides recommendations on policy frameworks, implementation of land pooling processes, and entry points for those donors that are active in the urban space.